Received Cradling Bias During the First Year of Life: A Retrospective Study on Children With Typical and Atypical Development - Malatesta, Gianluca; Marzoli, Daniele; Apicella, Fabio; Abiuso, Claudia; Muratori, Filippo; Forrester, Gillian S.; Vallortigara, Giorgio; Scattoni, Maria Luisa; Tommasi, Luca (Frontiers in Psychiatry, 2020)
A population-level left cradling bias exists whereby 60-90% of mothers hold their infants on the left side. This left biased positioning appears to be mutually beneficial to both the mother and the baby’s brain organization for processing of socio-emotional stimuli. Previous research connected cradling asymmetries and Autism Spectrum Disorders (ASD), entailing impairment in socio-communicative relationships and characterized by an early hypo-lateralization of brain functions. In this explorative study, we aimed to provide a contribution to the retrospective investigations by looking for early behavioral markers of neurodevelopmental disorders such as ASD. We hypothesized that an atypical trajectory in maternal cradling might be one of the possible signs of an interference in mother-infant socio-emotional communication, and thus of potential neurodevelopmental dysfunctions. To this aim, we examined photos depicting mother-child early cradling interactions by consulting family albums of 27 children later diagnosed with autism and 63 typically developing children. As regards the first half of the first year of life, no differences were shown between maternal cradling-side preferences in typical and ASD groups, both exhibiting the left-cradling bias in the 0-3 months period, but not in the 3-6 months period. However, our results show dissimilar patterns of cradling preferences during the second half of the first year of life. In particular, the absence of left-cradling shown in typical mothers was not observed in ASD mothers, who exhibited a significant left-cradling bias in the 6-12 months age group. This difference might reflect the fact that mother-infant relationship involving children later diagnosed with ASD might remain “basic” because mothers experience a lack of social activity in such children. Alternatively, it may reflect the overstimulation in which mothers try to engage infants in response to their lack of responsiveness and social initiative. However, further investigations are needed both to distinguish between these two possibilities and to define the role of early typical and reversed cradling experiences on neurodevelopment.